Nitride semiconductor light-emitting diodes (LEDs) : materials, technologies and applications - Huang, Jian-Jang; Kuo, Hao-Chung; Shen, Shyh-Chiang (Woodhead Publishing series in electronic and optical materials., 2013)
The development of nitride-based light-emitting diodes (LEDs) has led to advancements in high brightness LED technology for solid state lighting, handheld electronics and advanced bioengineering applications. Nitride semiconductor light-emitting diodes (LEDs) reviews fabrication, performance and applications of this technology that encompass the state-of-the-art material/device development and practical nitride-based LED design considerations. Part one reviews the fabrication of nitride semiconductor LEDs. Chapters cover molecular beam epitaxy (MBE) growth of nitride semiconductors, mod.